LGBT Prevention through Sex Education in Islam Qur'anic Perspective (Study of Parent-to-Child Communication) - Mhd Ibnu Hanan Al Faruqi; Rizka Fitriana; Surya Hidayat; Moh Taufikurrahman; Nasrulloh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education about sex for children must be carried out from an early age, the goal is to avoid sexual behavior that is not in accordance with the norms in society such as LGBT. One of the efforts that can be made is through the implementation of sex education in accordance with strong Islamic religious values. The approach used in this study is qualitative with a literature study method. The purpose of this study is to analyze the role of sex education in Islam according to the perspective of the Qur'an in preventing LGBT behavior in children, as well as to explore how communication between parents and children in the context of sex education can contribute to such prevention. Data collection techniques are in the form of collecting literature works, including scientific journals, books, articles related to research. The data analysis technique is through sorting and providing codes on the data that has been collected. The result is that the Qur'anic view of LGBT is haram. And it is forbidden to behave LGBT because it is considered a dangerous act and can cause serious diseases such as syphilis, hepatitis B, and HIV/AIDS. The conclusion of this study is that with all the adverse impacts that exist regarding LGBT behavior, it must be extra in providing sex education to children and stricter in applying the values of the teachings in the Qur'an.